Effect of salbutamol on oxygen saturation in bronchiolitis. Issue 9 (September 1991) - Ho, L; Collis, G; Landau, L I; Le Souef, P N
Abstract : Inhaled sympathomimetic agents are often used in bronchiolitis with little objective evidence of benefit. The arterial oxygen saturation (SaO2) reflects the adequacy of ventilation-perfusion balance. The aim of the current study was to determine the effect of inhaled salbutamol on SaO2. In a randomised, double blind study, 21 infants, admitted with bronchiolitis positive for respiratory syncytial virus, had continuous SaO2 measurements made before and after nebulised salbutamol or placebo. SaO2 was recorded over 30 minutes for a baseline, then during the 10 minutes of first nebulisation with either salbutamol or saline, then over 30 minutes after nebulisation, the 10 minutes of second nebulisation with the alternate regime, and another 30 minutes after this second nebulisation. Desaturation occurred after salbutamol and saline nebulisation. The fall in SaO2 with salbutamol was seen whether infants received it as the first or second nebulisation. The fall in SaO2 after saline was seen when given first, but not when given after salbutamol. The decrease in SaO2 was greater and more prolonged with salbutamol than with saline. Routine nebulised aerosol sympathomimetic treatment during acute bronchiolitis cannot be recommended.